2013
DOI: 10.1002/art.37777
|View full text |Cite
|
Sign up to set email alerts
|

PLD4 as a novel susceptibility gene for systemic sclerosis in a Japanese population

Abstract: Objective. Systemic sclerosis (SSc) is an autoimmune disease for which multiple susceptibility genes have been reported. Genome-wide association studies have shown that large numbers of susceptibility genes are shared among autoimmune diseases. Recently, our group identified 9 novel susceptibility genes associated with rheumatoid arthritis (RA) in a Japanese population. The aim of this study was to elucidate whether the 18 genes that displayed associations or suggestive associations for RA in our previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 44 publications
(59 reference statements)
3
58
0
Order By: Relevance
“…The expression of AHNAK2 is significantly upregulated in F4/80 hi mononuclear cells in murine SLE nephritis, suggesting AHNAK2 is a potential effector gene 33. However, we note that SNP rs4465542 links strongly with two proximal SNPs that have been reported for the risk of systemic sclerosis in Japanese samples within the PLD4 gene 34. Though the function of the PLD4 gene is poorly understood, we cannot rule out its possibility as a susceptibility gene for SLE.…”
Section: Discussionmentioning
confidence: 63%
“…The expression of AHNAK2 is significantly upregulated in F4/80 hi mononuclear cells in murine SLE nephritis, suggesting AHNAK2 is a potential effector gene 33. However, we note that SNP rs4465542 links strongly with two proximal SNPs that have been reported for the risk of systemic sclerosis in Japanese samples within the PLD4 gene 34. Though the function of the PLD4 gene is poorly understood, we cannot rule out its possibility as a susceptibility gene for SLE.…”
Section: Discussionmentioning
confidence: 63%
“…Recent studies showed two autoimmune diseases, sclerosis and rheumatoid arthritis, were related to PLD4 mutation (16,17). Although PLD4 seemed to have some immunological functions, little was known about its function in cells.…”
Section: Discussionmentioning
confidence: 99%
“…After treated with LPS, the expression of the PLD4 in microglia was increased which could promote the function of phagocytosis (15). Recent studies have indicated mutation in PLD4 gene was associated with two autoimmune diseases, named systemic sclerosis (16) and rheumatoid arthritis (17), both had abnormal inflammatory skin lesions symptoms (18). Although PLD4 was involved in microglia phagocytosis, there is little known on its function and the mechanism, thus PLD4 needed to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…A nonsense mutation in PLD4 (W215X) in Fleckvieh cattle causes severe skin lesions, generally poor health, and decreased survival ( 99 ). PLD4 defi ciency in humans has been linked through genome-wide association studies to syndromes such as rheumatoid arthritis ( 100 ) and the autoimmune disease systemic sclerosis ( 101 ). Taken together, these fi ndings suggest that PLD4 defi ciency results in hyper-activation of the immune system, causing a variety of autoimmune-like syndromes.…”
Section: Pld3mentioning
confidence: 99%